أسباب حوادث المرور على الطريق السيار شرق – غرب - متيجي,جمال Metidji Djamel; عيزل,نعيمة Aizel Naima (University of Eloued جامعة الوادي, 2025)
تهدف هذه الدراسة إلى تسليط الضوء على ظاهرة خطيرة تحصد سنويا عبر التراب الوطني ارواح عشرات المئات و تخلف عشرات الالاف من الجرحى الذين تستمر معاناة الكثير منهم طويلا و تستدعي حالاتهم متابعة و تكفل علاجي متعدد و ينظم الكثير منهم لفئة المعاقين ، انها ظاهرة حوادث المرور التي نسعى الى معرفة أسباب حدوثها في الطريق السيار ( شرق – غرب) من وجهة نظر سائقي: الحافلات و شاحنات الوزن الثقيل لنقل البضائع لتبيان و تحديد مسببات وقوع هذه الحوادث هل المسؤولية تقع على عاتق السائق أم المركبة أم نوعية الطريق ومحيطه؟ . Abstract: The purpose of this study is to bring to light a hazardous phenomenon that's happening all over the national territory, and which claims the lives of hundreds of people every year, leaving thousands more injured. The majority of these individuals suffer for a long period of time, necessitating various treatments and follow-ups. As a result, a significant number become disabled. The focus of this study is on understanding why road accidents occur on the east-west highway, specifically with regard to bus and truck drivers. The aim is to determine as follows: What are the causes? Is it the driver's responsibility, the vehicle, or the quality of the road and its surroundings?
من وجهة نظر سائقي الحافلات و الوزن الثقيل
Keywords: حوادث المرور; السائق; Road's accidents; Driver; Vehicle